Environmental Kuznets Curve (EKC): Empirical Relationship Between Economic Growth, Energy Consumption, and CO2 Emissions: Evidence from 3 Developed Countries - Beşe, Emrah; Kalayci, Salih (Panoeconomicus, 2021)
In this study, the environmental Kuznets curve (EKC) hypothesis is examined for 3 developed countries, which are Denmark, the United Kingdom, and Spain, for the period between 1960 and 2014. The EKC hypothesis is examined under 2 nexuses which are GDP, CO2 and energy consumption, and GDP, CO2, energy consumption and the square of GDP. Causal and long-term relationships between GDP, CO2, and energy consumption are examined for these 3 developed countries using the ARDL bounds test, the Toda and Yamamoto Granger non-causality test, the VAR Granger Causality/Block Exogeneity Wald test, and the Johansen cointegration test. Long-term relationships between GDP, CO2, energy consumption, and the square of GDP are examined by the Johansen cointegration test. The EKC hypothesis is not confirmed for Denmark, the United Kingdom, and Spain, and the neutrality hypothesis is confirmed for these 3 developed countries. Unidirectional causality running from energy consumption to CO2 is found for Denmark, and unidirectional causality running from CO2 to energy consumption is found for the United Kingdom.Key words: Environmental Kuznets curve, ARDL bounds test, Toda and Yamamoto Granger non-causality test, Developed countries.JEL: Q4, Q5, O5.